Transcriptional Regulators Cph1p and Efg1p Mediate Activation of the Candida albicans Virulence Gene SAP5 during Infection - Staib, Peter (American Society for Microbiology, 2002)
The opportunistic fungal pathogen Candida albicans can cause superficial as well as systemic infections. Successful adaptation to the different host niches encountered during infection requires coordinated expression of various virulence traits, including the switch between yeast and hyphal growth forms and secretion of aspartic proteinases. Using an in vivo expression technology that is based on genetic recombination as a reporter of gene activation during experimental candidiasis in mice, we investigated whether two signal transduction pathways controlling hyphal growth, a mitogen-activated protein kinase cascade ending in the transcriptional activator Cph1p and a cyclic AMP-dependent regulatory pathway that involves the transcription factor Efg1p, also control expression of the SAP5 gene, which encodes one of the secreted aspartic proteinases and is induced by host signals soon after infection. Our results show that both transcriptional regulators are important for SAP5 activation in vivo. SAP5 expression was reduced in a cph1 mutant, although filamentous growth in infected tissue was not detectably impaired. SAP5 expression was also reduced, but not eliminated, in an efg1 null mutant, although this strain grew exclusively in the yeast form in infected tissue, demonstrating that in contrast to in vitro conditions, SAP5 activation during infection does not depend on growth of C. albicans in the hyphal form. In a cph1 efg1 double mutant, however, SAP5 expression in infected mice was almost completely eliminated, suggesting that the two signal transduction pathways are important for SAP5 expression in vivo. The avirulence of the cph1 efg1 mutant seemed to be caused not only by the inability to form hyphae but also by a loss of expression of additional virulence genes in the host.